2019
DOI: 10.1007/s10803-019-04317-1
|View full text |Cite
|
Sign up to set email alerts
|

The Profiles and Correlates of Psychopathology in Adolescents and Adults with Williams, Fragile X and Prader–Willi Syndromes

Abstract: Psychopathology is prevalent in Williams (WS), fragile X (FXS) and Prader-Willi (PWS) syndromes. However, little is known about the potential correlates of psychopathology in these groups. A questionnaire study was completed by 111 caregivers of individuals with WS (n = 35); FXS (n = 50) and PWS (n = 26). Mean age was 26 years (range 12-57 years); 74 (67%) were male. Multiple regression analyses indicated that higher rates of health problems and sensory impairments predicted higher psychopathology in WS (p < .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Annette Karmiloff-Smith pioneered a cross-syndrome approach to the study of cognition in neurodevelopmental disorders (NDDs;Brown et al, 2003;Paterson et al, 2006;Scerif et al, 2004). Her cross-syndrome approach has advanced the understanding of a wide range of phenomena, including language development (Kelly et al, 2013;Lindgren et al, 2009), face and emotion recognition (Annaz et al, 2009;Dimitriou et al, 2015;Martínez-Castilla et al, 2015), attention (Cornish et al, 2012;Scerif et al, 2004), sleep (Ashworth et al, 2013(Ashworth et al, , 2017D'Souza et al, 2020), psychopathology (Rodgers et al, 2012;Royston et al, 2019;Woodcock et al, 2009), sensory processing (Hannant et al, 2018;Heald et al, 2020) and social/adaptive behaviour (Hamner et al, 2019;Sumner et al, 2016;Williams et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Annette Karmiloff-Smith pioneered a cross-syndrome approach to the study of cognition in neurodevelopmental disorders (NDDs;Brown et al, 2003;Paterson et al, 2006;Scerif et al, 2004). Her cross-syndrome approach has advanced the understanding of a wide range of phenomena, including language development (Kelly et al, 2013;Lindgren et al, 2009), face and emotion recognition (Annaz et al, 2009;Dimitriou et al, 2015;Martínez-Castilla et al, 2015), attention (Cornish et al, 2012;Scerif et al, 2004), sleep (Ashworth et al, 2013(Ashworth et al, , 2017D'Souza et al, 2020), psychopathology (Rodgers et al, 2012;Royston et al, 2019;Woodcock et al, 2009), sensory processing (Hannant et al, 2018;Heald et al, 2020) and social/adaptive behaviour (Hamner et al, 2019;Sumner et al, 2016;Williams et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there was a high prevalence of emotional and behavioral disturbances in these children and young people. Most previous studies report similarly high DBC overall scale and subscale scores (Dimitropoulos et al, 2009; Einfeld et al, 1999; Einfeld et al, 2014; O'Donoghue et al, 2005; Rice, Lagopoulos, et al, 2016; Richdale et al, 1999; Royston et al, 2020; Sarimski et al, 2012; Sinnema et al, 2011), although some of the continental studies reported lower scores (Jauregi et al, 2013; Salles et al, 2016; Steinhausen et al, 2002). The majority of respondents in the present study reported skin‐picking, a poor sense of danger, impulsivity, lying, temper tantrums, and other behaviors already described in the literature as typical of PWS (Dimitropoulos et al, 2009; Einfeld et al, 1999; Rice, Gray, et al, 2016; Sarimski et al, 2012; Steinhausen et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…This research is pivotal in understanding the multifaceted challenges faced by parents of children with developmental delays, specifically focusing on primary and secondary speech and language delays. In the context of developmental disorders, the study delves into the comparative analysis of parental stress in families of children with various syndromes, including Down, Williams, Fragile X, and Prader-Willi syndromes (16,17). This comparative approach is crucial as it highlights the differential impact of various developmental disorders on family dynamics.…”
Section: Discussionmentioning
confidence: 99%